Austempering Transformation Kinetics of Compacted Graphite Cast Irons Obtained by Mössbauer Spectroscopy - Desimoni, Judith (2001)
Mossbauer spectroscopy has been applied systematically to study the processes occurring during the Stage I of the austempering transformation of compacted graphite cast irons at temperatures from 573 to 673 K for two Mn concentrations. The kinetics of transformation (γ→αFe+γhc) was followed determining the dependence of the high-carbon austenite percentage on austempering time for different austempering temperatures and Mn contents. The evolution of the C concentration and the total amount of C incorporated into high-carbon austenite were also monitored. The results are compared with those of other morphologies and discussed in the frame of Johnson-Mehl's and diffusion models.